1975
DOI: 10.1017/s0021859600052588
|View full text |Cite
|
Sign up to set email alerts
|

The ‘teat order’ of suckling pigs: I. Relation to birth weight and subsequent growth

Abstract: SUMMARYTeat orders were determined for 76 litters of Large White and Large White × Landrace pigs. Regression analysis within litters revealed a relationship between suckling position and weight both at birth (P<0·01) and at 3 weeks of age (P<0·001), with the heavier piglets tending to occupy the more anterior teats. The correlation coefficients, however, were very small (r = –0·16 and –0·22 respectively). The correlation between birth weight and 3-week weight was much larger (r = +0·47); and a comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
41
0
3

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 6 publications
6
41
0
3
Order By: Relevance
“…However, between birth and weaning, the piglets that suckled anterior teats gained more weight than the other piglets, confirming results from other studies (FRASER & JONES, 1975;PLUSKE et al, 2007;SKOK et al, 2007;PEDERSEN et al, 2011). This can be attributed to a greater milk intake after birth in piglets that suckle anterior teats, as it has been shown that the anterior mammary glands of the sow tend to produce more milk than the posterior ones (BARBER et al, 1955;SKOK et al, 2007), and there is a correlation between milk intake and growth of piglets until the third week of nursing (BARBER et al, 1955).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, between birth and weaning, the piglets that suckled anterior teats gained more weight than the other piglets, confirming results from other studies (FRASER & JONES, 1975;PLUSKE et al, 2007;SKOK et al, 2007;PEDERSEN et al, 2011). This can be attributed to a greater milk intake after birth in piglets that suckle anterior teats, as it has been shown that the anterior mammary glands of the sow tend to produce more milk than the posterior ones (BARBER et al, 1955;SKOK et al, 2007), and there is a correlation between milk intake and growth of piglets until the third week of nursing (BARBER et al, 1955).…”
Section: Discussionsupporting
confidence: 89%
“…While some studies report that larger piglets establish themselves on anterior teats (FRASER & JONES, 1975), other studies support the current results (PLUSKE et al, 2007;SKOK et al, 2007). Some explanations about the preference for anterior teats are that the piglets that choose these teats are attracted by the vocalization of the sow, even before checking the quantity of milk available (JEPPERSEN, 1982), or that choice or discovery of a certain teat occurs randomly; after that, the setting of a fixed order would occur because piglets which defend the first teat it has established it after birth (SCHEEL et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Piglets will engage in antagonistic tussling within minutes of being born while teat order is disputed (Algers, 1993;Fraser & Jones, 1975;McBride, 1963). This early social interaction often determines future dominance and aggression levels among the litter, with piglets positioned at the anterior teats being more dominant and those in the middle teats fighting more frequently (Ruis et al, 2000;Sundman, 2011).…”
Section: Social Playmentioning
confidence: 99%
“…The initial research by on weight at 3 wk of age have produced vari- Donald (1931) and subsequent research able results with correlations ranging between (Barber et al 1955;Hartman et al 1962;0.03and -0.39(McBrideetal. 1965;Fraser Hemsworth et al 1976a) has demonstrated and Jones 1975;Hemsworth et al 1976a: that during the first 3 wk growth is limited Scheel etal. 1977 (Hemsworth etal.…”
mentioning
confidence: 96%
“…1976b (Scheel et al 1977). The socially dominant piglets are heavier at 3 wk of age (McBride et al 1965;Hartsock et al 1977;' Scheel et al 1917), and the heavier piglets suckle for longer periods of time (Hemsworth et al 1916a The feeding and management of the sows has been described previously (Dyck et al 1985 (Barber et al 1955;Fraser and Jones 1975;Fraser and Lin 1984;Fraser and Thompson 1986;McBride et al 1965 …”
mentioning
confidence: 96%